Три новых вида сверчков рода Sciobia (Orthoptera, Gryllidae) из Северной Африки - Горохов, А.В. (Вестник зоологии, 1985)
In order to escape the taxonomic difficulties, the genus Sciobisa Burm. is suggested to be considered sensu lato. Three species are described as new: S. natalia sp. n. (Morocco), S. maria sp. n. (Algier) and S. tatiana sp. n. (Algier). Type material is the property of Zoological Institute, USSR Academy of Sciences (Leningrad).